Sosialisasi Seminar Pengendalian Polusi Udara - mulya, widya; Sari, Iin Pratama; Siahaan, Jannes; Swandito, Adji (EUNOIA, 2022)
Air pollution is the entry or inclusion of substances, energy, and/or other components into the ambient air by human activities, so that the ambient air quality drops to a certain level which causes the ambient air to be unable to fulfill its function (Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia Nomor P.15/MENLHK/SETJEN/KUM.1/4/2019). Ten years ago, the World Bank predicted that global primary energy supply would increase by a factor of 1,6 to 3,5 then until 2050 and for developing countries this factor would range from 2,3 to 5,2, in projections BPPT-OEI 2016 for the 2015-2050 period, the factor of increasing primary energy supply is even greater, ranging from 5,3 to 6,8 8 (Badan Pengkajian dan Penerapan Teknologi, 2017). The 2015 World Climate Change Summit or UNFCCC COP21 held in Paris aims to keep the world’s average temperature rise below 20C, compared to pre-industrial temperatures and to encourage further efforts to increase the temperature to no more than 1,50C, at the conference Indonesia committed to reduce greenhouse gas (GHG) emissions by 26% by its own efforts and up to 41% with international assistance as outlined in the NDC (Nationally Determined Contribution) (Badan Pengkajian dan Penerapan Teknologi, 2017). Air pollution control can be carried out with strict supervision of clean energy development according to policies that have been issued by the government, create as many green open spaces as possible, especially with plants that have the characteristics of absorbing maximum amounts of pollutants, pollutant-prone areas such as cities and industries to complement pollutant sources with particulate control technology tools and gas control technologies.